Art Therapy for Groups : a Handbook of Themes, Games and Exercises. - Liebmann, Marian (Brunner-Routledge, 2004)
Art Therapy for Groups provides detailed guidance on how to set up and run a theme-based art therapy groups and discusses factors affecting different client groups.